A Tale of Two Seasons: Distinct Seasonal Viral Communities in a Thermokarst Lake - Valérie Langlois; Catherine Girard; Warwick F. Vincent; Alexander I. Culley (Microorganisms, 2023)
Thermokarst lakes are important features of subarctic landscapes and are a substantial source of greenhouse gases, although the extent of gas produced varies seasonally. Microbial communities are responsible for the production of methane and CO2 but the “top down” forces that influence microbial dynamics (i.e., grazers and viruses) and how they vary temporally within these lakes are still poorly understood. The aim of this study was to examine viral diversity over time to elucidate the seasonal structure of the viral communities in thermokarst lakes. We produced virus-enriched metagenomes from a subarctic peatland thermokarst lake in the summer and winter over three years. The vast majority of vOTUs assigned to viral families belonged to Caudovirales (Caudoviricetes), notably the morphological groups myovirus, siphovirus and podovirus. We identified two distinct communities: a dynamic, seasonal community in the oxygenated surface layer during the summer and a stable community found in the anoxic water layer at the bottom of the lake in summer and throughout much of the water column in winter. Comparison with other permafrost and northern lake metagenomes highlighted the distinct composition of viral communities in this permafrost thaw lake ecosystem.